Optimal Controller Design of Crowbar System Using Class Topper Optimization: Towards Alleviating Wind-Driven DFIGs Under Nonstandard Voltages - Elnaggar, Mohamed F. (Association for Scientific Computing Electronics and Engineering (ASCEE), 2025)
Increased integration of doubly fed induction wind generators (DFIWG), power sector deregulation, rising energy demands, and technological breakthroughs are all contributing to the rapid advancement of modern energy infrastructure. These advancements, nevertheless, pose serious challenges to maintaining fault ride-through capability (FRTC) in DFIWG. Thus, this work proposes a novel FRTC enhancement method that uses a crowbar system with a class topper optimization (CTO) based control technique. The crowbar system and DFIWG are integrated with the investigated system to achieve FRTC, reduce injected harmonic distortion, and maintain the DC link voltage (DCLV) below the permitted level. Additionally, the system has a DCLV control system that uses a CTO-PI controller to maintain an enclosure DCLV, which enhances crowbar performance. The findings demonstrated that when a CTO-based controller is employed, the DFIWG system reacts slightly better to angular speed, active and reactive power, DCLV, and generator speed. The MATLAB/Simulink scenarios used to test the suggested system show that it can achieve FRTC and allow for a high penetration potential of DFIWG.